1998
DOI: 10.1111/j.1439-0310.1998.tb00048.x
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile Richardson's Ground Squirrels (Spermophilus richardsonii) Manifest Both Littermate and Neighbour/Stranger Discrimination

Abstract: Newborn ground squirrels (Sprmniophilus spp.) are reared in isolation of individuals belonging to other litters. At or near weaning, they broaden their social interactions to encompass conspecifics other than littermates. In laboratory studies, juvenile ground squirrels commonly discriminate littermates from non-littermates, but few studies have examined whether behavioural discrimination at that level persists under natural circumstances. Previous studies have also all but ignored the possibility of alternati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…All juveniles in this study were from litters for which the mother was identified. Individuals from a single litter were assigned a coefficient of relatedness of 0.5, given we had only maternal relatedness data from our pedigree records, and because juveniles behaviourally discriminate littermates from non-littermates, even though some individuals were undoubtedly maternal half-siblings due to multiple paternity [44,45]. Neighbours were defined as individuals that had core areas adjacent to one another and nest burrows that were less than 30 m apart.…”
Section: Methodsmentioning
confidence: 99%
“…All juveniles in this study were from litters for which the mother was identified. Individuals from a single litter were assigned a coefficient of relatedness of 0.5, given we had only maternal relatedness data from our pedigree records, and because juveniles behaviourally discriminate littermates from non-littermates, even though some individuals were undoubtedly maternal half-siblings due to multiple paternity [44,45]. Neighbours were defined as individuals that had core areas adjacent to one another and nest burrows that were less than 30 m apart.…”
Section: Methodsmentioning
confidence: 99%
“…Both the social tuco‐tuco and Richardson’s ground squirrel share dense Oxtr binding in the medial amygdala; a region important for social recognition (Choleris et al, ; Ferguson, Aldag, Insel, & Young, ). Living in larger social groups, individuals could benefit from the ability to remember individuals they had previously interacted with—in Richardson’s ground squirrel this manifests as an ability to remember whether individuals are reliable in alarm call production when predators are present (Hare & Atkins, ), and in discriminating kin and familiar neighbors from unfamiliar individuals (Hare, ). Kin recognition constitutes an important component of Richardson's ground squirrel sociality (Hare, ; Hare & Murie, ), and influences alarm communication as Richardson’s ground squirrel females produce more alarm calls when surrounded by kin (Davis, ).…”
Section: Discussionmentioning
confidence: 99%
“…Sociality in Richardson's ground squirrel is essential for their survival, as these rodents issue alarm calls warning conspecifics of potential threats, thereby reducing predation risk among call recipients (Davis, 1984;Yeaton, 1972). Responses to these alarm calls vary based on the social environment (Davis, 1984;Hare, 1998b), the individual caller's past reliability (Hare, 1998a;Hare & Atkins, 2001), the type of call (Davis, 1984;Sloan, Wilson, & Hare, 2005), and also the positional and urgency information encoded within alarm calls (Sloan & Hare, 2004Warkentin, Keeley, & Hare, 2001). Richardson's ground squirrels are seasonal breeders, with mating in mid-through late-March and young emerging from natal burrows in late May through early June (Yeaton, 1972).…”
mentioning
confidence: 99%
“…In response, receivers exhibit a higher level of vigilance and are more likely to run to burrows in response to chirps than to whistles (Sloan et al, 2005). Richardson's ground squirrels are an excellent model for examining the neural mechanisms of perception of alarm calls due to the breadth of research which has examined behavioral responses to calls in varied contexts in the field (e.g., Hare, 1998b; Hare & Warkentin, 2012; Sloan et al, 2005; Swan & Hare, 2008a, 2008b; Wilson & Hare, 2003). In addition, while differences in rat and mouse strains are sometimes noted in communication work (Schwarting et al, 2018), free‐living Richardson's ground squirrels are outbred and behave similarly in widely dispersed populations (Davis, 1984; Downey, Jones, Quinlan, & Scrimgeour, 1994; Hare, 1998a).…”
Section: Introductionmentioning
confidence: 99%